HUBUNGAN ANTARA KEMANDIRIAN BELAJAR, SIKAP SISWA TERHADAP PEMBELAJARAN MATEMATIKA DAN KEMAMPUAN METAKOGNISI DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS X SEMESTER GENAP SMK MUHAMMADIYAH PRAMBANAN KABUPATEN SLEMAN TAHUN AJARAN 2015/2016 - Susanto, Doni; Khasanah, Uswatun (AlphaMath : Journal of Mathematics Education, 2017)
During this time some students get assumption that mathematics is a difficult lesson. The lowmathematics outcomes learning is considered having a relation with the self regulatedlearning, the students’ attitude towards the mathematics learning and the students’metacognition ability. This research is purposed to know is there or not about the positiverelation and significance between the self regulated learning, the students’ attitude towardsthe mathematics learning and the metacognition ability with the mathematics learningoutcomes of students of grade X in even semester in Muhammadiyah vocational school ofPrambanan in Sleman regency in the academic year of 2015/2016. The population in thisresearch is all of the classes of X TP (TPA, TPB, TPC, TPD) in Muhammadiyah vocationalschool of Prambanan. The sampling technique used is purposive sampling which is based onthe direction from the teacher and class X TPC is taken to be the sampling class. The datacollecting technique used is the questioner technique and test which is the determination andthe consistence is measured using the validity and reliabiliti test. Pre-test covers normalitytest, independence test, and linearity test. Meanwhile, data analysis for testing the hypothesisuses the regression and correlation analysis. The research’s result shows that there are thepositive relation and significance between the self regulated learning, the students’ attitudetowards the mathematics learning and the metacognition ability with the mathematics learningoutcomes.Keyword: Self Regulated Learning, Students’ Attitude towards the Mathematics Learning,Metacognition Ability, Mathematics Learning Outcomes